2013
DOI: 10.1016/j.krcp.2013.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Nondiabetic kidney diseases in type 2 diabetic patients

Abstract: BackgroundThe aim of this study was to evaluate the clinical characteristics of nondiabetic nephropathy in type 2 diabetes mellitus patients and to find a clinical significance of renal biopsy and immunosuppressive treatment in such a patient.MethodsRenal biopsy results, clinical parameters, and renal outcomes were analyzed in 75 diabetic patients who underwent kidney biopsy at Chungnam National University Hospital from January 1994 to December 2010.ResultsThe three most common reasons for renal biopsy were ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The incidence of these NDRDs varies between 18% and 80% among different studies based on the indication used for renal biopsy [ 10 , 11 ]. MN is a common primary glomerular disease seen in diabetic patients [ 6–8 ]. Others include IgA nephropathy, focal segmental glomerulosclerosis, membranoproliferative glomerulonephritis and minimal change disease [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of these NDRDs varies between 18% and 80% among different studies based on the indication used for renal biopsy [ 10 , 11 ]. MN is a common primary glomerular disease seen in diabetic patients [ 6–8 ]. Others include IgA nephropathy, focal segmental glomerulosclerosis, membranoproliferative glomerulonephritis and minimal change disease [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Membranous glomerulopathy is a common cause of primary glomerular disease in diabetics [ 6–8 ]. It can occur either as an isolated lesion or superimposed with diabetic nephropathy (DN).…”
Section: Introductionmentioning
confidence: 99%
“…However, not every patient with DM proceeds to renal insufficiency caused by DKD, but also caused by other GNs. Many previous studies showed that the proportion of NDKD was high, at up to 83%, although the ranges were broad [22,23]. Because of this heterogeneous nature, it is hard to predict the progression of renal insufficiency in diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a significant proportion of patients with DM have non-DKD (NDKD). Previous studies showed that the prevalence of NDKD ranged from 3% to 83% among patients undergoing renal biopsies [12][13][14][15][16][17][18][19][20][21][22][23]. The prognosis of patients with DKD tends to be worse than those with NDKD, and appropriate treatment is different for each disease.…”
Section: Kidney Biopsy Can Help To Predict Renal Outcomes Of Patients...mentioning
confidence: 99%
“…Renal biopsy is required only in specific circumstances when an NDKD is suspected [Table 2]. [112] Various forms of glomerular diseases may superimpose on DN. [12] Histologically, DN is characterized by excessive accumulation of extracellular matrix with mesangial expansion and glomerular basement membrane thickening.…”
Section: Discussionmentioning
confidence: 99%